2010
DOI: 10.4236/jwarp.2010.23027
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Isoproturon Pesticide on C, N and S Doped TiO2

Abstract: TiO2 doped with C, N and S (TCNS photocatalyst) was prepared by hydrolysis process using titanium iso-propoxide and thiourea. The prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photo electron spectroscopy (XPS), BET surface area, FTIR and diffuse reflectance spectra (DRS). The results showed that the prepared catalysts are anatase type and nanosized par-ticles. The catalysts exhibited stronger absorption in the visible light region with a red shift in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Increase of the synthesis temperature from 25 ºC to 80 ºC (RTO-1 and RTO-2) did not affect the particle morphology, but the presence of water in the reaction medium (RTO-3) resulted in the formation of larger particles (Figure 1). The particles obtained under the other synthesis conditions presented morphology similar to that shown in Figure 2, consistent with the literature 32,33 and showing that doping with nitrogen did not alter the morphology of the TiO 2 .…”
Section: Scanning Electron Microscopysupporting
confidence: 78%
“…Increase of the synthesis temperature from 25 ºC to 80 ºC (RTO-1 and RTO-2) did not affect the particle morphology, but the presence of water in the reaction medium (RTO-3) resulted in the formation of larger particles (Figure 1). The particles obtained under the other synthesis conditions presented morphology similar to that shown in Figure 2, consistent with the literature 32,33 and showing that doping with nitrogen did not alter the morphology of the TiO 2 .…”
Section: Scanning Electron Microscopysupporting
confidence: 78%
“…According to Fig. 3 and the reported energy band gap in the Table 3, the red shift in the DRS spectrum increases and band gap energy shows a decrease with an increase in the content of doped elements in TiO 2 network, which improves light adsorption and optical activity of TiO 2 catalysts 45 . The morphology and size distribution of Mn, Mo, La/TiO 2 /AC nanocomposite were investigated by FE-SEM (Fig.…”
Section: Selection Of Photocatalystmentioning
confidence: 86%
“…2 . The absorption bands of 3100-3700 cm -1 and 1600-1640 cm -1 were assigned to the stretching vibration and bending vibration, respectively, of the hydroxyl groups present on the surface of TiO 2 catalyst 45 . Peaks in the regions of 3434.43 cm -1 and 1608.48 cm -1 were respectively related to the bond stretching and bending -OH groups caused by the adsorbed water molecules and hydroxyl groups.…”
Section: Selection Of Photocatalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, DTA analysis studies reported on TiO 2 using thiourea as a precursor illustrates the role of dopant on the calcination temperature [11][12][13][14]. In the present investigation, the main focus is on shifting the absorption edge of TiO 2 to the visible light region by introducing C, N, and S into the TiO 2 lattice structure.…”
Section: Introductionmentioning
confidence: 97%